ĐẶC TRƯNG CƠ BẢN CỦA CÁC ĐỚI ĐỨT GẪY HOẠT ĐỘNG CHÍNH VÙNG TÂY BẮC VIỆT NAM - Thúy, Nguyễn Ngọc; Chính, Vũ Văn; Phách, Phùng Văn (Vietnam Journal of Earth Sciences, 2005)
Described features of the main active zones in the Northwestern of Vietnam are follow : name of fault zones, grade, azimuth, length, depth, direction and slope of slip surfaces, mechanism of movement in Pliocene - Quaternary and recent time, intensity and cumulating stress capacity causing earthquake. The results show that: 1. The northwest-southeast fault systems had played main role in main active fault system in Northwestern of Vietnam. 2. All main active zones in the Northwestern of Vietnam have abrupt slip surfaces varied from 60° to 90°. From ·the end of Eocene up to now the activity of the mentioned fault zones consist of two phases in strike-slip stress field. Right strike-slip movements of the northwest-southeast fault systems were relative to the Pliocene-Quaternary sub-meridian extended basins. 3. Activity of the fault zones in recent time are not equal along the fault, for example, in the Son La fault zone the northwest segment is the most active, while the middle is the less one and southeast is medium. 4. High speed shear movement of the northwest-southeast fault systems is main cause for formatting of the structures cumulating high stress, especially in the ends or interactions of the different azimuth segments along the Son La, Song Ma, Pu May Tun fault zones inducing high grad earthquake.